Location, location: understanding the metastatic microenvironment - Neta Erez (Molecular Oncology, 2023)
Mortality from cancer is almost exclusively a result of tumor metastasis. Since advanced metastatic cancers are incurable, understanding the biology of tumor metastasis is one of the most significant challenges in cancer research today. A large body of research had established the central role of the microenvironment in facilitating tumor growth. However, the role of the metastatic microenvironment in supporting the multistage process of metastasis is still largely unresolved. To thrive at the metastatic site, disseminated cancer cells must adapt to distinct organ‐specific microenvironments that exert unique cellular and molecular interactions to oppose or support the growth of metastatic cancer cells. Understanding these intricate interactions is key to the development of effective therapeutic strategies that may prevent metastatic relapse.